Novel bone-targeted parathyroid hormone-related peptide antagonists inhibit breast cancer bone metastases - Ponnapakkam, Tulasi; Anbalagan, Muralidharan; Stratford, Jr, Robert E; Rowan, Brian G; Gensure, Robert C (Anti-cancer drugs, 2021)
Patients with advanced breast cancer often develop bone metastases. Treatment is limited to palliative care. Parathyroid hormone (PTH)/parathyroid hormone-related peptide (PTHrP) antagonists for bone metastases failed clinically due to short half-life and inadequate concentration in bone. We synthesized two novel PTHrP antagonists fused to an inert bacterial collagen binding domain (CBD) that directs drugs to bone. PTH(7-33)-CBD is an N-terminal truncated PTHrP antagonist. [W2]PTH(1-33)-CBD is an PTHrP inverse-agonist. The aim of this study was to assess PTH(7-33)-CBD to reduce breast cancer bone metastases and prevent osteolytic destruction in mice and to assess both drugs for apoptosis of breast cancer cells in vitro and inhibition of PTH receptor (PTHR1). PTH(7-33)-CBD (1000 µg/kg, subcutaneous) or vehicle was administered 24 h prior to MDA-MB-231 breast cancer cell inoculation into the tibia marrow. Weekly tumor burden and bone density were measured. Pharmacokinetic analysis of PTH(7-33)-CBD in rat serum was evaluated. Drug effect on cAMP accumulation in SaOS-2 osteosarcoma cells and apoptosis of MDA-MB-231 cells was assessed. PTH(7-33)-CBD reduced MDA-MB-231 tumor burden and osteolytic destruction in mice 4-5 weeks post-treatment. PTH(7-33)-CBD (1000 μg/kg i.v. and subcutaneous) in rats was rapidly absorbed with peak concentration 5-min and terminal half-life 3-h. Bioavailability by the subcutaneous route was 43% relative to the i.v. route. PTH(7-33)-CBD was detected only on rat periosteal bone surfaces that stained positive for collagen-1. PTH(7-33)-CBD and [W2]PTH(1-33)-CBD (10-8M) blocked basal and PTH agonist-induced cAMP accumulation in SaOS-2 osteosarcoma cells. Both drugs induced PTHR1-dependent apoptosis of MDA-MB-231 cells in vitro. Novel bone-targeted PTHrP antagonists represent a new paradigm for treatment of breast cancer bone metastases.